ANALISIS KINERJA APARATUR SIPIL NEGARA PADA BADAN PENGEMBANGAN SUMBER DAYA MANUSIA DAERAH PROVINSI NUSA TENGGARA TIMUR - Mau Tae, Gregorius (AKSIOMA : Jurnal Manajemen, 2022)
The purpose of this study was to determine the description of the performance, work motivation, work discipline, organizational culture, work environment, and HR competencies at the Regional Human Resources Development Agency (BPSDMD) of NTT Province. To determine work discipline partially, corporate culture, work environment, and HR competence have a positive and significant effect on ASN work motivation at BPSDMD NTT Province. To find out partially work discipline, organizational culture, work environment, HR competence, and work motivation positively affect ASN performance at BPSDMD NTT Province. Work has a positive and significant impact in mediating the influence of work discipline, organizational culture, work environment, and HR competence on ASN performance at BPSDMD NTT Province. This research uses quantitative methods. The sample of this research is the staff of BPSDMD NTT Province, as many as 55 people. Data were collected using a questionnaire and analyzed using the SmartPLS application. The inner model test shows that work discipline, organizational culture, work environment, and HR competence partially positively and significantly affect work motivation. Because the probability values ??of work discipline, corporate culture, work environment, HR competence, and work motivation partly have a positive and significant effect on employee performance. The Specific Indirect Effect test results show that work motivation has a positive and significant impact in mediating the influence of work discipline, organizational culture, work environment, and HR competence on ASN performance.